Digital democracy: transforming political communication in Indonesia - Widodo, Suko; Kristiyono, Jokhanan (Jurnal Studi Komunikasi, 2025)
Abstract This article explored the political communication environment in Indonesia from 2004 to 2024, which is solely within the reform era. Focusing on how technology shapes democratic engagement, the study examined how the digital media revolution has affected political communication over the last 20 years. A comprehensive literature evaluation was carried out, combining knowledge from 122 scholarly works. Further sources were included to fully substantiate the study's assertions because the initial bibliography only had 28 references. The study examines how digital and traditional media interact in Indonesia, emphasising how social media sites like Facebook, Twitter, and WhatsApp are becoming increasingly important in public debate, political campaigns, and grassroots organising. Bypassing conventional gatekeepers, these platforms have allowed voters to communicate directly with political leaders; nevertheless, they have also brought up problems like disinformation and digital inequality. The results show that although digital platforms and big data have chances to improve democratic processes, their use has frequently been flimsy and unduly formalistic, with little effect on systemic political participation. This study also emphasised the necessity for a customised approach to deal with enduring problems such as disinformation, divisive content, and the digital divide. In Indonesia's reform era, these issues remain significant obstacles to widespread political involvement. The conclusion suggests that governments, media outlets, and civil society actors work together to use digital technologies inclusively and morally, ensuring that these instruments support democratic governance rather than exacerbate the already-existing disparities. More studies are needed to close the gap between theoretical frameworks and real-world implementations in Indonesia's dynamic political communication environment.